Elimination of iron from acidic mine drainage (AMD) in the co-treatment with poultry wastewater through a sulfate-reducing bioreactor - Hải, Nguyễn Thị; Hằng, Đinh Thuý (Vietnam Journal of Biotechnology, 2016)
Acid mine drainage (AMD) is contaminated water from mining indistry, characterized by low pH (1 – 4) and high concentration of heavy metals (up to thousands ppm). AMD is highly toxic to aquatic life and soil ecology surrounding the mining areas, therefore should be treated adequately before discharging to the environment. The treatment technology based on sulfate-reducing bioreactors has been applying widely with high efficiency. Sulfate-reducing bacteria (SRB) stand at the central point of the technology, use hydrogen and organic carbons to reduce sulfate to sulfde, that involve in metal precipitation and pH neutralization. For establishing the technology, sources of SRB as well as organic substrates neccesary for the bacteria should be acquired from outside. In many cases, these two requirements can be supplied from cow manure and agriculture residues (such as rice straws) added to the bioreactor before operating. In the present study, a mixed culture of SRB enriched from aquaculture-processing wastewater was used to start up the sulfate-reducing bioreactor for the AMD-treatment laboratory model. Cotreatment of AMD and poultry wastewater in this model operated under continuous mode with retention time of 48 h allowed to remove 85 – 88% Fe2+ in the AMD (from the original concentration of 200 mg/L). Study of the bacterial community via DGGE analyses of the 16S rDNA fragments showed that the enrichment culture consisted of three main SRB genera Desulfovibrio, Desulfomicrobium and Desulfobulbus spp., whereas in the sediment of the bioreactor only Desulfovibrio spp were found dominating. The obtained results would serve as basis for the development of biological-based technology to treat AMD together with organic-rich wastewater sources, suitable for mines located closely to residential areas.